An Investigation of Cancer Rates in the Argentia Region, Newfoundland and Labrador: An Ecological Study. (8th November 2015) - Duke, Pauline; Godwin, Marshall; Peach, Mandy; Fortier, Jacqueline; Bornstein, Stephen; Buehler, Sharon; McCrate, Farah; Pike, Andrea; Wang, Peizhong Peter; Cullen, Richard M.
Abstract : Background . The Argentia region of Newfoundland and Labrador, Canada, was home to a US naval base during a 40-year period between the 1940s and the 1990s. Activities on the base resulted in contamination of the soil and groundwater in the region with chemicals such as heavy metals and dioxins, and residents have expressed concern about higher rates of cancer in their community. This study investigated the rate of cancer diagnosis that is disproportionately high in the Argentia region. Methods . Cases of cancer diagnosed between 1985 and 2011 were obtained for the Argentia region, two comparison communities, and the province of Newfoundland and Labrador. Crude and age-standardized incidence rates of cancer diagnosis were calculated and compared. The crude incidence rate was adjusted for differences in age demographics using census data, and age-standardized incidence rates were compared. Results . Although the Argentia region had a higher crude rate of cancer diagnosis, the age-standardized incidence rate did not differ significantly from the comparison communities or the provincial average. Argentia has an aging population, which may have influenced the perception of increased cancer diagnosis in the community. Conclusions . We did not detect an increased burden of cancer in the Argentia region.